2008
DOI: 10.1158/1541-7786.mcr-07-0391
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of Hypoxic Immature Dendritic Cells: Modulation of Chemokine/Receptor Expression

Abstract: Hypoxia is a condition of low oxygen tension occurring in inflammatory tissues. Dendritic cells (DC) are professional antigen-presenting cells whose differentiation, migration, and activities are intrinsically linked to the microenvironment. DCs will home and migrate through pathologic tissues before reaching their final destination in the lymph node. We studied the differentiation of human monocytes into immature DCs (iDCs) in a hypoxic microenvironment. We generated iDC in vitro under normoxic (iDCs) or hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 65 publications
8
91
2
1
Order By: Relevance
“…As in previous publications, 31,32 genes were defined as being differentially regulated in hypoxia if they exhibited more than 1.5-fold increase in gene expression (Table 1) or down-regulated if they showed less than 0.67-fold change (Table 2) compared with normoxic cultures. A comparison of our human MDM microarray results (Tables 1-2) with those obtained previously for related human myeloid cell types exposed to hypoxia (monocytes and monocyte-derived dendritic cells 31,32 ) shows that some genes were seen to be regulated by all 3 cell types (up-regulated: VEGFA, CXCR4, TNF-␣, TIMP1, PHD3, aldolases A and C, enolase 2, TREM1, NCF1; down-regulated: cathepsin C). However, some genes regulated by hypoxia in MDMs are not similarly regulated by hypoxia in these other 2 cell types, such as IL-1␤, IL-12p40, Ang-2, endothelin 1, STATS 4 and 6, CCLs 3 and 5, CCR7, HMOX1, and hsp70 (up-regulated) and CD36, PECAM1 (CD31), HIF-2␣, and MHCII DM␤; down-regulated; Tables 1-2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous publications, 31,32 genes were defined as being differentially regulated in hypoxia if they exhibited more than 1.5-fold increase in gene expression (Table 1) or down-regulated if they showed less than 0.67-fold change (Table 2) compared with normoxic cultures. A comparison of our human MDM microarray results (Tables 1-2) with those obtained previously for related human myeloid cell types exposed to hypoxia (monocytes and monocyte-derived dendritic cells 31,32 ) shows that some genes were seen to be regulated by all 3 cell types (up-regulated: VEGFA, CXCR4, TNF-␣, TIMP1, PHD3, aldolases A and C, enolase 2, TREM1, NCF1; down-regulated: cathepsin C). However, some genes regulated by hypoxia in MDMs are not similarly regulated by hypoxia in these other 2 cell types, such as IL-1␤, IL-12p40, Ang-2, endothelin 1, STATS 4 and 6, CCLs 3 and 5, CCR7, HMOX1, and hsp70 (up-regulated) and CD36, PECAM1 (CD31), HIF-2␣, and MHCII DM␤; down-regulated; Tables 1-2).…”
Section: Resultsmentioning
confidence: 99%
“…Some were seen to also be regulated by hypoxia in monocytes and immature dendritic cells (VEGFA, GLUT1, and CXCR4). 31,32 However, others, such as IL-1␤, ADORA2A, and STAT4, were only altered in hypoxic macrophages. These differences could be the result of variations in the severity and/or duration of hypoxia applied to cells 31,32 and/or may reflect differences in the transcription factors used by these 3 cell types in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In agreement with our observation on the enhanced inflammatory functions acquired by DCs in hypoxia, Ricciardi et al recently demonstrated that hypoxic DCs express functional CCR3, CCR2, CX3CR1, and CXCR4. 36 In contrast with DCs, it was reported in breast cancer cells that the hypoxia-mimicking compounds DFX and cobalt chloride induce functional CCR7, mainly through a posttranscriptional mechanism. 37 Our data suggest that, in response to various TLR agonists, hypoxia promotes a "premature DC phenotype" characterized by enhanced inflammatory functions (high TNF␣ and IL-1␤ production), selective homing capacity to peripheral tissues (through sustained CCR5 expression), and impaired migration in response to lymphoid-specific chemokines (CCL19).…”
Section: Discussionmentioning
confidence: 99%
“…DC are considered to play an important role in tumor immuno-surveillance by eliciting tumor-specific T cells responses. Recent evidence, however, indicates that DC might also contribute to tumor angiogenesis by releasing proangiogenic factors, like VEGF and IL-8, in response to hypoxia (Ricciardi et al, 2008). Human tumor cells implanted together with immature DC have enhanced tumor vascularization and growth, while mature DC did not impact angiogenesis (Fig.…”
Section: Other Myeloid Cell Subpopulationsmentioning
confidence: 98%